Health, Climate, and Climate Change in Arid Zones - Lloyd, Simon J; Kovats, R Sari (Annals of Arid Zone, 2016)
Human health is affected by climate and weather both directly and indirectly. Glebal climate change is expected to have overall negative health impacts, with the burden mostly borne by people living in low- and middle-income countries. Research has not focused explicitly on arid zones, but inferences can be made regarding impacts of likely importance, particularly those related to water scarcity, which is projected to increase in many areas. Diarrhea - which is strongly linked to water availability - remains a major killer of young children, and can have long-term health impacts on those surviving multiple episodes. Crop productivity is projected to decrease in many low latitude areas and is likely to place many millions at risk of malnutrition, mostly children. In Africa, meningitis epidemics are associated with dry climates, although vaccine availability may reduce future burdens. Climate influences the distribution and seasonality of malaria, and climate change will expand some malarious areas and decrease others; much uncertainty remains due to the importance of local non-climatic factors in determining incidence. Reducing the health impacts of climate and climate change requires diverse actions from within and beyond the health sector. Importantly, most actions will have wider benefits, including poverty reduction. Key words: Climate, climate change. diarrhea. health, malaria, malnutrition, meningitis.